Accessibility in online exhibitions of Brazilian science museums and centers: identifying strategies and barriers - Norberto Rocha, Jessica; Marinho, Letícia; Heck, Gabriela; Carmo, Marcelle Pita de Sousa; Abreu, Willian Vieira de (Frontiers in Education, 2025)
Science museums and exhibitions play a crucial role in formal and non-formal education and in the communication of science. However, access to online science exhibitions is still limited. This exploratory study aims to map and analyze the accessibility of online exhibitions provided by Brazilian science museums and centers during the COVID-19 pandemic. The investigation was based on the 69 Brazilian museums mapped in the Guide to Accessible Science Centers and Museums of Latin America and the Caribbean. By combining navigation and keyword searches on these institutions’ online communication channels, 101 online exhibitions were identified. We divided the analysis into two phases, descriptive and analytical, for identifying the provision of accessibility strategies and assistive technology resources. Out of the 101, 94 exhibitions, presented at 25 museums, provided at least one accessibility resource. The analysis revealed that 87 exhibitions featured keyboard compatibility, 29 included narration, 13 offered video captions, six provided Brazilian sign language interpretation, five had audio description resources, and two contained alternative text for images. The online exhibitions shared their content through various types of media, which necessitate different assistive resources and accessibility options. When examining the relationship between media and accessibility strategies, we can emphasize that exhibitions featuring a variety of media and assistive resources offer greater potential for accessibility. However, this occurs in a very limited number of exhibitions. This gap in accessibility can affect the opportunities for people with disabilities to access non-formal education, science communication, and culture. While we identified accessible online exhibitions covering various themes and areas of knowledge, as well as a few good practices for inclusion, there is still significant progress to be made. There is a demand for increased accessibility in online exhibitions and for a greater number of museums to offer them. We recognize that this task is challenging, as it requires a multidisciplinary and multi-professional effort. We propose that accessibility and inclusion be made integral to the planning and execution of new online exhibitions from the outset, as the involvement of professionals and visitors with disabilities in this process will foster a more equitable and inclusive education.